The expression level of the CLDN14 gene in patients with urolithiasis - a preliminary report - Słota, Diana; Wasilewski, Tadeusz Paweł; Goniewicz, Mariusz; Długoborska, Klaudia (Journal of Education, Health and Sport, 2019)
SummaryAim: An attempt to assess the expression of the CLDN14 gene at the mRNA level in patients diagnosed with urolithiasis in relation to healthy persons constituting a comparative group.Material and methods: The material for examinations was peripheral blood from 23 patients, including 12 women and 11 men with diagnosed kidney stones disease and 6 donors (control group), including 2 women and 4 men who did not have kidney stones.Results and conclusions: The studies showed differences in the level of CLDN14 gene expression in both the examined and the comparative group.Key words: CLDN14, gene expression, urolithiasis